Employee Development: Analysis Organization Culture, Competence and Mentoring: A Literature Review - Siti Annisa Wahdiniawati; Rubadi; Nia Sarinastiti; Supardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this article with variables in the field of Human Resources is to see that there have been previous research results from various articles around the world with one other variable as independent and dependent. The results of this scientific article for the three variables together have not been discussed with or without the object of research, so this article can make a reference material for science and knowledge, especially in the field of human resources.